Improving the quality and content of discharge summaries on acute medicine wards: a quality improvement project. Issue 2 (7th April 2022) - Scarfield, Phoebe; Shepherd, Thomas David; Stapleton, Caitriona; Starks, Alexandra; Benn, Ellen; Khalid, Sara; Dayment, Bryony; Moate, Alex; Mohamed, Sandra; Lee, Jasmine
Abstract : Discharge summaries are important medical documents that summarise a patient's hospital admission. The Royal College of Physicians provides standardised guidance on the content of discharge summaries, given their important role as a handover document to general practitioners (GPs). Our project started in June 2020 on an acute medical ward, where significant variation had been noted in the quality and content of discharge summaries. A multidisciplinary team (MDT) was formed including doctors, nurses and hospital/community pharmacists, as well as a patient representative, to ensure active patient co-design. The problem was scoped by asking GPs to provide feedback via surveys and process mapping. Our aim was to increase the compliance of discharge summaries with 10 core criteria from a baseline of 55% to 95% by June 2021. Change ideas were developed by the MDT and were tested using plan–do–study–act (PDSA) cycles that included additional pharmacy support, a discharge summary template and individualised feedback. The project reached its goal of 95% compliance in January 2021, 5 months ahead of the target date, and this improvement has been sustained since. The project expanded to a second acute medical unit ward in May 2021. The expanded project reached its goal of 90% compliance within 6 weeks and maintained sustained improvement with further PDSA cycles. A standard operating procedure has been created to help embed the changes on these wards. Our future aims are to redesign and improve the current electronic system and to help spread positive changes throughout the Trust.